Toward a Relational View of Organizational Innovation: Learning from Previous and Subsequent Stages of Innovation in Large Biopharmaceutical Firms, 1990–2006. (1st June 2020) - Dahlin, Eric
Abstract : The paper draws on insights from relational sociology to develop a relational view of organizational innovation which suggests that feedback between stages of innovation may occur regardless of whether they precede one another, and activities at different stages may have reciprocal effects. Regression models based on a sample of 113 large biopharmaceutical firms demonstrate that firms with products in alternative stages of innovation are associated with having products in the focal stage. The key findings from the regression analysis are that product development generates positive feedback for product implementation and vice versa, and engaging in activities at multiple, alternative stages simultaneously generates benefits at the focal stage. The reciprocity between stages provides compelling evidence for the importance of viewing innovation through the lens of relational theory. Interviews with industry informants illustrate the fluidity that exists between innovation stages and the importance of fostering social interactions and communication between organizational members involved in innovation for fostering success across stages.